On Inverse Sturm- Liouville Problems With Symmetric Potentials - Tuz, Munevver (E D P Sciences, 2017)
In this paper an inverse problem -y'' + p(x)y = lambda y y'(0) - hy(0) = y'(1) + hy(1) = 0 where P are integrable on [0, 1] and satisfy the symmetry conditions p(x) = p(1 - x) almost everywhere in the interval 0 <= x <= 1. We reconstruct the potential of the inverse Stunn Liouville problem's solution is obtain for finite interval with symmetric potential.
2nd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 20-22, 2017 -- Istanbul, TURKEY
Keywords: Inverse problem symmetric potential; fixed point theorem; second-order differential equation